2019
DOI: 10.24840/2184-0954_003.002_0007
|View full text |Cite
|
Sign up to set email alerts
|

Driving simulator for evaluating the effects of road geometric design on driver behavior

Abstract: The traditional approach adopted towards road safety is the analysis of risk factors that contribute to frequency or severity of traffic crashes. Many distinct elements play a role, simultaneously, in a crash occurrence, and, undoubtedly, geometric design of highways and its effect on human behavior are part of that equation. A valuable tool to investigate this interaction is the driving simulator. Nevertheless, experiment design, participants’ features, and data acquisition are detrimental factors for the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…Therefore, thes studies on road geometry are different from our research. After summarizing related publications such as [29][30][31][32][33], we found that research process or results were identical to those in our study. Among those publications, the horizontal curve was the leading research topic.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Therefore, thes studies on road geometry are different from our research. After summarizing related publications such as [29][30][31][32][33], we found that research process or results were identical to those in our study. Among those publications, the horizontal curve was the leading research topic.…”
Section: Resultssupporting
confidence: 73%
“…Consequently, through a triple cross-analysis, the index set that could represent the driving control characteristics in different road types was obtained, as shown in Figure 20. We can draw the following conclusions: After summarizing related publications such as [29][30][31][32][33], we found that no research process or results were identical to those in our study. Among those publications, th horizontal curve was the leading research topic.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Then, for each study, the qualification of the 15 criteria as a set will be analyzed to assign a final classification between Strong, Moderate, or Weak. The classification is based on the ranges of scores presented in Table 2, which in time is computed for each study by applying the equation 1, which is a function of the possible response options for each criterion [26]:…”
Section: Risk Of Bias In Individual Studiesmentioning
confidence: 99%